Pengaruh Solvabilitas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Pertambangan Logam Dan Mineral Lainnya Yang Terdaftar Di BEI - Asri, Rahmatul; Idris, Hariany; Afiah, Nur (Bongaya Journal of Research in Accounting (BJRA), 2023)
This study aims to determine the effect of solvency on profitability in metal and other mineral mining sub-sector companies listed on the Indonesian stock exchange. The variable of this research is profitability as the dependent variable (Y) as measured byreturn on investment, and solvency as the independent variable (X) as measured bydebt to asset ratio. The population of this study is all metal and other mineral mining sub-sector companies listed on the Indonesian stock exchange in 2018-2021 as many as 11 companies, while the sample is 8 metal and other mineral mining sub-sector companies on the Indonesian stock exchange which were taken using thepurposive sampling. Data collection was carried out using documentation techniques. Data analysis was performed by normality test, simple regression test, hypothesis test which consisted of the coefficient of determination test and the individual parameter significant test (statistical t test). The results showed that, based on the results of the t test, the solvency value of t was obtainedcount >ttablenamely -3.394> 2.042 and a significance value of 0.02 <0.05. This shows that solvency has a significant negative effect on profitability so that the hypothesis is accepted.